Brief Cognitive Behavioral Therapy for an Adult Woman with Depression Who Receives Antidepressant Medication - Faradiba, Andi Tenri; Kurniawan, Fenny (Faculty of Psychology, Universitas Gadjah Mada, 2025)
Depression profoundly disrupts interpersonal relationships and impairs daily functioning. It is primarily associated with dysregulation of key neurotransmitter systems, making pharmacological intervention essential. Evidence indicates that combining pharmacotherapy with cognitive behavioral therapy (CBT) produces superior outcomes compared to pharmacotherapy alone in managing depression. This case study examines the application of CBT alongside antidepressant medication in the treatment of a 26-year-old woman working in the financial sector who experienced chronic anxiety and pervasive feelings of inadequacy. Her cognitive distortions led her to interpret neutral stimuli as threatening. The administration of quetiapine improved her sleep quality and enhanced emotional resilience under stress. Subsequently, she completed four brief online CBT sessions, which resulted in significant cognitive restructuring and enabled her to critically evaluate and modify negative automatic thoughts in daily life. As a result, she demonstrated greater self-efficacy and developed a more positive self-concept. This case contributes to the growing body of evidence supporting the effectiveness of combined pharmacotherapy and CBT in reducing depressive symptoms among adult women.